Emergency calls reveal the importance of arrests in reducing repeat domestic violence - Sofia Amaral; Gordon B. Dahl; Timo Hener; Victoria Kaiser; Helmut Rainer (EconPol Forum, 2023)
Domestic violence is a pervasive threat to women's well-being worldwide and many victims are repeatedly abused by their partners. One possible but controversial police measure to deal with this problem is to arrest suspects immediately on the spot. Geo-coded 999 emergency call data can be used not only to identify victims and repeat offenders, but also to monitor the impact of officers' actions at the scene. Recent research shows that arresting the marginal suspect is effective and reduces the number of repeat assaults by about 50 percent in the following year. Arrests contribute to a cooling-off period in the short term, in addition to deterring abuse in the long term.
Keywords: 330